2003
DOI: 10.1007/s00122-003-1504-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of resistance to the geminivirus, Bean dwarf mosaic virus, and the role of the hypersensitive response in common bean

Abstract: Bean dwarf mosaic virus (BDMV) is a single-stranded DNA virus (genus: Begomovirus, family: Geminiviridae) that infects common bean ( Phaseolus vulgaris L.) and causes stunted plant growth, and mosaic and mottle symptoms in leaves. BDMV shows differential pathogenicity in common bean, infecting germplasm of the Andean gene pool (e.g., the snap bean cultivar Topcrop), but not that of the Middle American gene pool (e.g., the pinto bean cultivar Othello). Resistance to BDMV in Othello is associated with developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…2), but results of coagroinfiltration studies in common bean indicated that it was not the dominant BDMV R gene from cv. Othello (19). A similar finding came from BDMV infection studies performed in RT4-4 transgenic N. benthamiana.…”
Section: Discussionsupporting
confidence: 73%
“…2), but results of coagroinfiltration studies in common bean indicated that it was not the dominant BDMV R gene from cv. Othello (19). A similar finding came from BDMV infection studies performed in RT4-4 transgenic N. benthamiana.…”
Section: Discussionsupporting
confidence: 73%
“…1, Cooley et al, 2000; 2, Ren et al, 2000; 3, Takahashi et al, 2001; 4, Takahashi et al, 2002; 5, Takahashi et al, 2004; 6, Sekine et al, 2006; 7, Chisholm et al, 2000; 8, Whitham et al, 2000; 9, Decroocq et al, 2009; 17, Provvidenti and Hampton, 1992; 18, Ma et al, 2010; 25, Moury and Verdin, 2012; 30, Grube et al, 2000; 31, Tomita et al, 2008; 32, Tomita et al, 2011; 33, Matsumoto et al, 2008; 34, Sawada et al, 2004; 43, De La Cruz et al, 1997; 44, Holmes, 1937; 45, Berzal-Herranz et al, 1995; 50, Anagnostou et al, 2000; 65, Hayes et al, 2004; 66, Hajimorad and Hill, 2001; 67, Hajimorad et al, 2005a; 68, Wen et al, 2013; 69, Eggenberger et al, 2008; 105, Whitham et al, 1994; 106, Erickson et al, 1999; 107, Baker et al, 1995; 108, Dinesh-Kumar et al, 1995; 109, Dinesh-Kumar et al, 2000; 110, Padgett and Beachy, 1993; 111, Padgett et al, 1997; 127, Vallejos et al, 2006; 128, Ariyarathne et al, 1999; 129, Collmer et al, 2000; 130, Kelly et al, 1995; 131, Kyle et al, 1986; 132, Fisher and Kyle, 1994; 133, Fisher and Kyle, 1996; 134, Zhou et al, 2007; 135, Garrido-Ramirez et al, 2000; 136, Seo et al, 2004; 137, Seo et al, 2007; 138, Wang et al, 1999; 139, Gururani et al, 2012; 156, Seo et al, 2006; 158, Yang et al, 2003; 159, Rai, 2006; 160, Harper et al, 2010; 166, Hanson et al, 2000; 167, Verlaan et al, 2013; 169, Ishibashi et al, 2007; 170, Ishibashi et al, 2012; 171, Pelham, 1966; 172, Yamafuji et al, 1991; 173, Meshi et al, 1988; 174, Kato et al, 2013; 179, Finlay, 1953; 180, Holmes, 1948; 181, Brommonschenkel et al, 2000; 182, Hallwass et al, 2014; 183, Hoffmann et al, 2001; 188, Hall, 1980; 189, Meshi et al, 1989…”
Section: Dominant Resistancementioning
confidence: 99%
“…Furthermore, the sources of resistance to BGMV were also effective against BDMV. A single dominant gene, Bdm, conferred BDMV resistance in crosses between Othello and Topcrop bean cultivars (Seo, Gepts, & Gilbertson, 2004).…”
Section: Common Mosaic and Black Rootmentioning
confidence: 99%